THE CORRELATION AMONG RELIGIOUS TOURISM, FOREIGN LANGUAGE USAGE, AND TOURIST MOTIVATION AT BUNDA BEACH AND RESORTÂ - Waruwu, Yestanius; Waruwu, Wince Lenta Viska Putri; Telaumbanua , Syukur Prima; Harefa, Afore Tahir (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2024)
This research examines the correlation among religious tourism, the use of foreign languages, and tourist motivation at Bunda Beach and Resort. The background of this research highlights the importance of information in foreign languages in religious tourism destinations which can influence tourists' experiences and motivation. The aim of this research is to understand the dynamics and factors that influence religious tourism, especially the use of Latin at Bunda Beach and Resort. The research method used is a mixed method, with data collection through questionnaires and interviews. The research results show that the use of Latin at Bunda Beach and Resort is not the main factor that attracts tourists. The main motivation of tourists to visit this place is to freshen up, pray and enjoy the religious atmosphere offered by the resort. The conclusion of this study is that although the use of Latin provides a strong religious overtone, this does not significantly influence tourist motivation. Bunda Beach and Resort management can consider adding other elements that are more attractive to general tourists.